Waterlogging as an environmental filter to tree recruitment in tropical wet grasslands - Ribeiro, Jonathan Wesley Ferreira [UNESP]; Gonçalo, Rafael Reis [UNESP]; Kolb, Rosana Marta [UNESP] (CSIRO Publishing, 2021)
Wet grasslands from the Brazilian Savanna (Cerrado) are open-canopy vegetation dominated by subshrubs and herbaceous plants. Although they frequently occur between gallery forests and savannas, tree species are rarely observed colonising these grasslands. Here, seed germination and seedling development of Cerrado trees under waterlogging conditions were evaluated in order to elucidate how soil waterlogging constrains tree regeneration in tropical wet grasslands. We used seeds of 11 representative Cerrado tree species that have different requirements for soil moisture (non-flooded v. flooded environments). Short periods (15 days) of waterlogging drastically decreased or inhibited germination and seedling development in four species, whereas long periods (30-45 days) of waterlogging reduced or inhibited germination and seedling development in 6 of the 11 species. As expected, we found fewer waterlogging-resistant seeds associated with those species from non-flooded environments. By contrast, more waterlogging-resistant seeds were associated with species that eventually or typically occur in flooded environments. Our results suggest that soil waterlogging is an important environmental filter constraining tree recruitment in tropical wet grasslands. However, some species can overcome this environmental filter by possessing waterlogging-resistant seeds or avoid it by establishing in less waterlogged locations.
Keywords: Brazilian grassland; Cerrado; flood tolerance; flooding; seasonal waterlogging; seed germination; seedling development; tropical savannas; vegetation mosaics